2018
DOI: 10.1177/0271678x18762645
|View full text |Cite
|
Sign up to set email alerts
|

20-HETE synthesis inhibition promotes cerebral protection after intracerebral hemorrhage without inhibiting angiogenesis

Abstract: 20-HETE, an arachidonic acid metabolite synthesized by cytochrome P450 4A, plays an important role in acute brain damage from ischemic stroke or subarachnoid hemorrhage. We tested the hypothesis that 20-HETE inhibition has a protective effect after intracerebral hemorrhage (ICH) and then investigated its effect on angiogenesis. We exposed hippocampal slice cultures to hemoglobin and induced ICH in mouse brains by intrastriatal collagenase injection to investigate the protective effect of 20-HETE synthesis inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 49 publications
1
40
0
Order By: Relevance
“…A total of 24 animals were used in this study. Animals and slice cultures for each group were randomized with the website www.randomization.com ( 32 , 33 ). This study was carried out in accordance with the recommendations of ARRIVE guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 24 animals were used in this study. Animals and slice cultures for each group were randomized with the website www.randomization.com ( 32 , 33 ). This study was carried out in accordance with the recommendations of ARRIVE guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…Primary cortical neurons were prepared from the pups of pregnant C57BL/6 mice at 15–18 days’ gestation. The website Randomization.com (http://www.randomization.com) was used to assign animals into different study groups [25,33]. …”
Section: Methodsmentioning
confidence: 99%
“…In the first set of experiments, 159 rats (180 rats were used, 21 rats died) were randomly [33] divided into the following groups: sham + vehicle, sham + 20 mg/kg SalB, SAH + vehicle, SAH + 10 mg/kg SalB, SAH + 20 mg/kg SalB, and SAH + 40 mg/kg SalB. Rats were killed at 24 and 72 h after SAH.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…d) was chosen for the present study. These animals were randomly divided into three groups (Han et al, 2019), as shown in Figure 1: (1) sham-operated (sham) group (n = 36), (2) ICH + vehicle group (n = 36), and (3) ICH + DHI group (n = 36). Animals in the ICH + DHI group were intraperitoneally administered with DHI on days 1, 3, and 7 after ICH (n = 12).…”
Section: Drug Administrationmentioning
confidence: 99%